2007
DOI: 10.1016/j.jcrs.2006.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with intraocular lens materials: Does heavy silicone oil act like silicone oil?

Abstract: Heavy silicone oil acted the same as silicone oil and covered the entire surface of silicone IOLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Similar observations of early cataract and adhesion of HSO to the posterior capsule or intraocular lenses have been reported by others in clinical and experimental observations [22,38,53].…”
Section: Limitations Of Heavy Silicone Oilsupporting
confidence: 89%
“…Similar observations of early cataract and adhesion of HSO to the posterior capsule or intraocular lenses have been reported by others in clinical and experimental observations [22,38,53].…”
Section: Limitations Of Heavy Silicone Oilsupporting
confidence: 89%
“…The least coverage was on the heparin-surface-modified lenses (mean score 9.4%). Yaman et al 109 looked at the effects of heavy silicone oil and found it to be akin to normal silicone oil. The mean heavy silicone oil coverage was 7.05% ± 7.88% on PMMA IOLs, 100% on silicone IOLs, 12.17% ± 11.43% on hydrophobic acrylic IOLs, and 34.64% ± 13.28% on hydrophilic acrylic IOLs.…”
Section: Surface Depositions/degradations/coatings Of Iolsmentioning
confidence: 99%